2018
DOI: 10.1111/joic.12525
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after use of covered stents to treat coronary artery perforations. Comparison of old and new‐generation covered stents

Abstract: Time to deliver was shorter with the PL-CS and resulted in lower rate of pericardial effusion and cardiac arrest. However, there were no significant differences in procedural success and 1-year follow-up MACE in patients treated with PL-CS or PTFE-CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…Unfortunately, the lower profile covered stents have not translated into greater procedural success; there was no difference in deliverability between the Graftmaster Rx (Abbott Vascular) and Aneugraft Dx (ITGI Medical, Santa Clara, CA) in this study. These results are in line with another study that retrospectively compared the Jostent Graftmaster (Abbott Vascular) PTFE covered stent with PK Papyrus stent (BIOTRONIK) in the treatment of CAP and found that while the newer PK Papyrus stent had shorter time to delivery and resulted in a lower rate of pericardial effusion and cardiac arrest, there was no difference in procedural success and 1‐year follow‐up MACE …”
supporting
confidence: 86%
“…Unfortunately, the lower profile covered stents have not translated into greater procedural success; there was no difference in deliverability between the Graftmaster Rx (Abbott Vascular) and Aneugraft Dx (ITGI Medical, Santa Clara, CA) in this study. These results are in line with another study that retrospectively compared the Jostent Graftmaster (Abbott Vascular) PTFE covered stent with PK Papyrus stent (BIOTRONIK) in the treatment of CAP and found that while the newer PK Papyrus stent had shorter time to delivery and resulted in a lower rate of pericardial effusion and cardiac arrest, there was no difference in procedural success and 1‐year follow‐up MACE …”
supporting
confidence: 86%
“…Given the need for both immediate and sustained sealing of the perforation to prevent hemodynamic collapse, covered stents represent the most common method to treat the site of hemorrhage when initial conservative measures (e.g., prolonged balloon inflation) fail. Although perforation management with stents using pericardial or venous covering has been described, the most commonly used covered stent consists of a single polytetrafluoroethylene (PTFE) layering between two coaxial 316L stainless steel, slotted‐tube balloon expandable stents (Graftmaster, Abbott Vascular, Santa Clara, CA; References ). However, the larger crossing profile (1.63–1.73 mm) limits guide catheter compatibility, and the two‐stent layer design challenges deliverability through tortuous and calcified anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one previous series of patients treated with the PK Papyrus stent has been reported. In a retrospective, observational study of 61 patients treated for coronary perforation over a 5 year period, 22 patients received the PK Papyrus stent, and 39 patients were treated with PTFE‐covered stents . Procedural success was numerically, but not significantly higher with the PK Papyrus stent (86% versus 69%, p = .22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study retrospectively compared the Jostent Graftmaster (Abbott Vascular, Santa Clara, CA) PTFE covered stent with PK Papyrus stent (BIOTRONIK, Berlin, Germany) in the treatment of coronary artery perforation and found that the newer PK Papyrus stent had shorter time to delivery and resulted in a lower rate of pericardial effusion and cardiac arrest. However, there was no difference in procedural success and 1‐year follow‐up MACE …”
mentioning
confidence: 91%